PENGARUH INTELLECTUAL CAPITAL TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING (STUDI KASUS PADA PERUSAHAAN YANG TERGABUNG DALAM JAKARTA ISLAMIC INDEX) - Lindawati Lindawati; Yulianto Yulianto (Sekolah Menengah Kejuruan (SMK) Pustek, 2021)
This study aims to determine the effect of Human Capital (VAHC), Physical Capital (VACA), Structural Capital (STVA) on Firm Value (PBV) and to determine the indirect effect of financial performance (ROE) as a mediator on companies incorporated in Jakarta Islamic. index on the Indonesia Stock Exchange for the period 2016-2019. This research is a quantitative study using panel data, which is a combination of time series and cross section data. The calculation results obtained show that the model used is Fixed Effect. Simultaneous analysis results show that VAHU, VACA, STVA have no significant effect on firm value. Based on the results of the partial analysis, Human Capital (VAHC) has no effect on firm value, Physical Capital (VACA) has no effect on firm value and Structural Capital (STVA) has no effect on firm value. And for the intervening variable in the form of financial performance, an analysis results that indirectly financial performance cannot mediate between the Intellectual Capital variable and Firm Value.